(untitled) (Marketing Journal, 2026)
Abstract This article presents a comprehensive analysis of the current state of the Samarkand regionʼs construction industry and its development trends. The study examined the volume of construction work completed in the region, the construction of residential and social infrastructure facilities, the level of development of the building materials industry, and investment activity indicators. Urban development projects, the use of innovative and digital technologies, export potential, and future development trends were also analyzed. The articleʼs findings allow us to determine the impact of the Samarkand regionʼs construction industry on the regional economy and its role in sustainable development. Keywords: Samarkand region, construction sector, urban development, infrastructure, investment, building materials, housing construction, innovation, economic development, sustainable growth.